Evaluating the Impact Performance of Environmentally Friendly Asphalt Concrete Slabs Containing Different Proportions of Recycled Concrete Aggregate and Corrugated Steel Fibers - Walid Mansour; Diaa Ashraf; Ali Basha (International Journal of Concrete Structures and Materials)
Abstract The current research focuses on recycling construction waste by producing asphalt concrete mixtures containing varying proportions of recycled concrete aggregate (RCA), ranging from 0 to 50%. To ensure the improvement of the asphalt mixtures' properties in terms of Marshall stability, flow, bulk density, air void ratio, and splitting tensile strength, steel fibers were added at a volume fraction of 1.0%. The experimental program consisted of 12 asphalt cylinders with a diameter of 102 mm and a height of 64 mm, cast with different asphalt mixtures to study the effects of varying RCA proportions as well as the addition of steel fibers on the mechanical properties of the asphalt concrete mixtures. The stability of the asphalt mixtures decreased by 17.6%, 23.2%, and 28.8% when RCA was used at ratios of 30%, 40%, and 50%, respectively, compared to the reference mixture. The Marshall stability of asphalt mixtures containing steel fibers was higher than that of their counterparts without fibers. Moreover, 12 asphalt slabs were cast with different ratios of RCA in preparation for testing under the impact load resulting from the free fall of a 10-kg steel mass from a height of 2 m. The results revealed that the ratio between the back and front crater diameters for slabs containing 10%, 20%, 30%, 40%, and 50% RCA after incorporating steel fibers was 1.15, 1.17, 1.15, 1.28, and 1.36, respectively. These ratios were smaller than those of the counterpart slabs without steel fibers by 18%, 19%, 19%, 7%, and 18%, respectively. Moreover, due to the low accuracy of existing mathematical models for predicting the penetration depth of asphalt slabs made with RCA, this research presents a developed mathematical model capable of accurately predicting the penetration depth of such slabs. This model considers both the ratio of RCA and the steel fibers within the asphalt mixtures.